An unusual record of Cuniculus paca in the state of Michoacán, Western México - Mijangos-Betanzos, Alejandro; Campos-Echeverría, Karina Herlinda; Carbajal-Navarro, Aglaen Lucero; Díaz-Rodríguez, Daniel; Mendoza Ramírez, Eduardo (Therya Notes, 2025)
This note reports on the camera-trapping recording of Cuniculus paca in the El Bejuco community in the municipality of Lázaro Cárdenas on the coast of Michoacán. This location is approximately 500 km from the nearest reported records. As part of the monitoring efforts associated with releasing a Tamandua mexicana specimen, four camera traps were set up on the Proyecto Maloca property in El Bejuco from March to May of 2024. We unexpectedly recorded the presence of a Cuniculus paca on nine different days; it appeared to be a juvenile. These records were concentrated in two of the four cameras set up at the site, which were 500 meters apart between 22:26 and 05:06 hr. Given the distance at which these records were obtained from the species’ known distribution, we hypothesize that human intervention likely facilitated the arrival of this C. paca individual to the monitored area. However, it is necessary to monitor the presence of this species and enhance monitoring in regions where information on their mammal community is lacking.